Exploring the Dynamics of Conflict: The Case of Tuah Sarumpun Dance Studio and the Government of Nagari Limau Lunggo Solok Regency - Haqqi, Iqbal Rahmatull; Ernida, Ernida; Erlinda, Erlinda; Nursyirwan, Nursyirwan (Gondang: Jurnal Seni dan Budaya, 2024)
This paper discusses the problem of Conflict Analysis between the art group Tuah Sarumpun and the Government of Nagari Limau Lunggo, Lembang Jaya District, Solok Regency. This case occurred because of the disharmonious communication between the Nagari government and the Tuah Sarumpun group. This problem continued and escalated when the Nagari government established a new group by providing facilities and financial support to ensure the health of the group. This triggered a conflict between the two camps. However, the conflict had a positive impact. For sanggar Tuah Sarumpun, the conflict can help maintain their social structure in the community. In fact, the conflict can also unite group members and reaffirm their group as members of sanggar Tuah Sarumpun. Their group identity as members of sanggar Tuah Sarumpun is positive. This research is classified as qualitative research that produces descriptive data. Related to that, the data collection methods used were interviews, observations, document studies, and group discussions. For the analysis of the main study is using conflict theory. As Corser (2010: 126) says, conflict is not only seen from the negative side, but positively conflict helps maintain social structures. Also, conflict can positively strengthen groups.